Modeling hydrocarbon generation of the Wenchang formation in Zhu III Sub-basin, Pearl River Mouth Basin South China by confined pyrolysis. Issue 1 (November 2020) - Li, S X; Liu, J Z; Li, Y C; Li, S Q
Abstract: The Zhu III Sub-basin is an important petroliferous basin in the Pearl River Mouth Basin. To obtain the evolution of liquid and gaseous hydrocarbon of the kerogen in the Zhu III Sub-basin, a sample of Wenchang formation in the sub-basin was used in the confined pyrolysis experiments in the present study. The results show that the kerogen has very good hydrocarbon generation potential, with the maximum ΣC1 -C5 and ΣC6+ yields of 999.69ml/g·TOC and 808.71mg/g·TOC, respectively, at 600°C. To further study the process of the process of hydrocarbon generation in geological conditions of the sub-basin, the burial, temperature, and thermal history are reconstructed. The kerogen of Wenchang formation started to generate oil and gas at 37Ma and 25Ma, respectively. The transformation ratio value of ΣC6+ reached 100% at 14.45Ma, and that of ΣC1 -C5 reached 37%, mainly ΣC2 -C5, at present.